The Relationship between Knowledge Factors, Reproductive Health Conditions and Age on Readiness to Have a Family in Young Women - Fibrila, Firda -; Ridwan, M. -; Herlina, Herlina - (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
In Indonesia, marriages between children under the age of 16 are around 1.8% and the percentage of marriages between children under 15 years is 0.6%. In Lampung Province, based on records at the Bandar Lampung High Religious Court (PTA), cases of early marriage in 2020 were relatively similar to those in 2021, where there were 240 cases as of May 2021. Meanwhile in Metro City, 15 cases were recorded, which is ranked 2nd in number. all cases in all districts/cities in Lampung Province. Adjustments to roles and duties for partners, especially at the beginning of marriage, certainly have the potential to cause problems and conflicts for couples. Lack of self-readiness to carry out new tasks which leads to divorce is one of the causes of difficulty in carrying out new tasks. In 2022, there were 17,043 divorce cases recorded in Lampung, an increase from 16,110 divorces in 2021, meaning that during 2022 there will be an increase of 933 cases compared to 2021. The aim of this research is to determine the relationship between knowledge, age and reproductive health conditions on readiness to have a family among young women in Metro City. The research design was cross sectional and used a sample of 163 people with an age range of 15-24 years. Sampling was taken using Simple Random Sampling using the incidental sampling technique. Data are presented with frequency tables and cross tables then analyzed using the Chi Square test. The results of the study showed that 56.5% of adolescent girls had less knowledge about family readiness, 39% of adolescent girls had reproductive health problems, 83.1% of adolescents in the reproductive age group were at risk and 51.5% of adolescent girls stated that they were not ready to have a family. . The results of the correlation analysis show that there is a relationship between adolescent girls' knowledge and family readiness with p-value = 0.042 (? alpha), there is a relationship between adolescent reproductive health conditions and family readiness with p-value = 0.000 (? alpha) and there is a relationship between adolescent age and readiness married with p-value = 0.000 (? alpha). It is necessary to form youth classes as an information and education communication (KIE) effort and a screening effort for prospective brides and grooms, especially young women.